2005
DOI: 10.1111/j.1365-2265.2005.02359.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in insulin sensitivity without concomitant changes in body composition and cardiovascular risk markers following fixed administration of a very low growth hormone (GH) dose in adults with severe GH deficiency

Abstract: Summary Objective  Untreated GH‐deficient adults are predisposed to insulin resistance and excess cardiovascular mortality. We showed previously that short‐term treatment with a very low GH dose (LGH) enhanced insulin sensitivity in young healthy adults. The present study was therefore designed to explore the hypothesis that LGH, in contrast to the standard GH dose titrated to normalize serum IGF‐I levels (SGH), may have differing effects on insulin sensitivity, body composition, and cardiovascular risk marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 66 publications
3
41
4
Order By: Relevance
“…Insulin concentrations and the HOMA-IR index increased after GH replacement in our patients, although no changes were observed in fasting plasma glucose. Recently, some authors found no changes or impairment in insulin sensitivity after short-term GH treatment (11,12) while, in contrast to our findings, other reports described an improvement in insulin sensitivity after GH therapy (10,23). No relationship between PAPP-A and glucose homeostasis parameters was found in our patients.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Insulin concentrations and the HOMA-IR index increased after GH replacement in our patients, although no changes were observed in fasting plasma glucose. Recently, some authors found no changes or impairment in insulin sensitivity after short-term GH treatment (11,12) while, in contrast to our findings, other reports described an improvement in insulin sensitivity after GH therapy (10,23). No relationship between PAPP-A and glucose homeostasis parameters was found in our patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Highly sensitive C-reactive protein (hsCRP), an acute-phase protein produced predominantly by hepatocytes under the influence of cytokines, such as interleukin-6 (IL-6), has been validated as one of the best cardiovascular risk markers (21). Some studies have demonstrated that GH replacement in GHD adults has beneficial effects on peripheral markers of inflammatory activity such as plasma hsCRP, IL-6 and fibrinogen (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…However, as IGF-I levels are determined by insulin secretion (Holly et al 1989), cause and effect may be difficult to identify, yet IGF-I may be a determinant of insulin secretion (Kulkarni et al 2002;Xuan et al 2002). This hypothesis can be tested and aetiological trials are currently being carried out in the MRC Ely cohort to look at the effects of low-dose growth hormone, which lead to small increases in IGF-I levels (Yuen et al 2005), on insulin secretion and the risk for the development of impaired glucose tolerance (Yuen et al 2004).…”
Section: Maintenance Of B-cell Massmentioning
confidence: 99%
“…Withdrawal from such treatment could therefore be beneficial and account for some of the cardiovascular variables that are improved after 60-month observation. Recently, it has been reported that GH treatment in very low dose (approximately onetenth of the one we have used) enhances insulin sensitivity with no apparent effects on body composition, lipolysis, and other surrogate cardiovascular risk markers in adults with severe acquired GHD (28). Lowdose short-acting GH regimen could have different vascular effects.…”
Section: Discussionmentioning
confidence: 99%